2017
DOI: 10.1103/physrevlett.119.057801
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Deformation of Azobenzene-Modified Liquid Crystal Polymers under Dual Wavelength Exposure: A Photophysical Model

Abstract: Azobenzene-embedded liquid crystal polymers can undergo mechanical deformation in response to ultraviolet (UV) light. The natural rodlike trans state azobenzene absorbs UV light and isomerizes to a bentlike cis state, which disturbs the order of the polymer network, leading to an anisotropic deformation. The current consensus is that the magnitude of the photoinduced deformation is related to the statistical building up of molecules in the cis state. However, a recent experimental study [Liu and Broer, Nat. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The wave speed can be further enhanced by an increase in actuation frequency, which has been observed for a glassy azobenzene-embedded LC polymer by a slight addition of visible light and temperature increase, 38 attributed to a boosted cis-to-trans isomerization. Furthermore, a moderate addition of visible light is found to enhance the total lightinduced strains due to the additional effect of continuous transcis-trans isomerization cycles, 29,45,46 leading to wave amplitudes that can be a factor of 4 higher. Thus, we expect that the modulation and frequency can be further enhanced leading to larger wave speeds and amplitudes and thus a higher flow efficiency for peristaltic microfluidic propulsion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wave speed can be further enhanced by an increase in actuation frequency, which has been observed for a glassy azobenzene-embedded LC polymer by a slight addition of visible light and temperature increase, 38 attributed to a boosted cis-to-trans isomerization. Furthermore, a moderate addition of visible light is found to enhance the total lightinduced strains due to the additional effect of continuous transcis-trans isomerization cycles, 29,45,46 leading to wave amplitudes that can be a factor of 4 higher. Thus, we expect that the modulation and frequency can be further enhanced leading to larger wave speeds and amplitudes and thus a higher flow efficiency for peristaltic microfluidic propulsion.…”
Section: Discussionmentioning
confidence: 99%
“…25 In the current study, however, we explore their effect on the generation of travelling waves. The attenuation length d t is inversely proportional to the concentration of the azobenzene added to the LC polymer and falls typically in the sub-micrometer range for heavily-dozed polymers, 24 and in the range from a few micrometers 25,29,58 to a few tens of micrometers 59 for systems with relatively low azo-dosages. Thicknesses of LC films fall in the range from a few to tens of micrometers.…”
Section: Light Attenuation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the three-phase line dynamically pins to traveling surface undulations, we show that the fluids in the channel can be transported. Such undulations can be generated by using moving light sources over light-responsive liquid crystal polymers [17,18,[22][23][24], by alternating heating and cooling of responsive hydrogels embedded in elastic channel walls [25], or by utilizing vacuum-pressed thin polymer films on a moving structured belt [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have revealed that the generation of free volume is largely enhanced by the oscillation of the LC polymer network using the dynamic trans–cis–trans isomerization of azobenzene by the illumination of 365 and 455 nm light with proper light intensity regulation (Figure 5a‐ii). [ 100,101 ]…”
Section: Switchable Topographies Of Coatings Adhered On Substratesmentioning
confidence: 99%